Prognostic factors in atypical carcinoid tumors - Şahin, Ahmet Bilgehan; Çubukçu, Erdem; Deligönül, Adem; Ocak, Birol; Melek, Huseyin; Erkan Ozmarasali, Buket; Caner, Burcu; Bayram, Ahmet; Akyıldız, Elif Ülker; Evrensel, Türkkan (The European Research Journal, 2023)
Objectives: Carcinoid tumors are rare neuroendocrine neoplasms of the lung. Although typical and atypical carcinoids have different clinical courses, most studies in the literature evaluate them together. Therefore, we aimed to investigate prognostic factors in patients with atypical carcinoids, excluding typical carcinoids. Methods: We included 32 patients with atypical carcinoids according to WHO 2021 criteria admitted to Uludag University Hospital. We retrospectively extracted the clinicopathological characteristics from electronic medical records. The log-rank tests were used to determine the prognostic factors on survival. Results: Median age was 57 (24-71) years. Pathological stages were as follows: stage I in 41%, II in 9%, III in 34%, and IV in 16%. Median Ki-67 index was 11% (1-50). Median follow-up time was 46.2 (0.7-184.2) months. 12-month and 48-month disease-free survival (DFS) rates were 92.3% and 79.2%, respectively. 12-month and 48-month overall survival (OS) rates were 93.8% and 86.2, respectively. Receiver operating characteristic curve analysis determined the Ki-67 cut-off as 12.5%. The log-rank test indicated that Ki-67 and stage were statistically significant prognostic factors for DFS and OS. The patients with a Ki-67 index lower than 12.5% had longer DFS and OS (p = 0.007 and p = 0.020, respectively). Conclusions: The Ki-67 index and 8th TNM staging have prognostic value on DFS and OS in patients with atypical carcinoids. Large-scale studies are needed to define the optimal cut-off value of Ki-67.